Stend dlja testirovanija i opredelenija tenzogeometriceskich charakteristik lyž - Ryazanov, A. G.; Ryazanov, A. A.; Dogov, A. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
In this paper, we analyze the problem of determining the tensogeometric characteristics of skis. The analysis of open information from manufacturers of ski equipment. A new stand has been introduced for testing and determining the tensogeometric and frequency characteristics of skis. A description of the prototype ski testing stand, and the software is given, its main features and functional features are determined.